2009
DOI: 10.1111/j.1365-2893.2008.01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of CIGB‐230, a therapeutic DNA vaccine preparation, in HCV‐chronically infected individuals in a Phase I clinical trial

Abstract: Hepatitis C virus (HCV) is a worldwide health problem. No vaccine is available against this pathogen and therapeutic treatments currently in use are of limited efficacy. In the present study, the immunogenicity of the therapeutic vaccine candidate CIGB-230, based on the mixture of pIDKE2, a plasmid expressing HCV structural antigens, with a recombinant HCV core protein, Co.120, was evaluated. CIGB-230 was administered by intramuscular injection on weeks 0, 4, 8, 12, 16 and 20 to 15 HCV-chronically infected ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 49 publications
(62 reference statements)
2
48
1
1
Order By: Relevance
“…Abundant evidence indicates that the immune system fails to eliminate virus from the liver in a large number of HCV-infected patients, and as a result, most acute infections lead to long-term viral persistence (12,36). The efficacies of therapeutic vaccination for chronic hepatitis C nonresponder patients are correlated with the inhibition of IFN-␥ secretion (3,18,34). Our results revealed that HCV NS5A affects Gata-3 and Tbx21 expression and impairs IFN-␥ production (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Abundant evidence indicates that the immune system fails to eliminate virus from the liver in a large number of HCV-infected patients, and as a result, most acute infections lead to long-term viral persistence (12,36). The efficacies of therapeutic vaccination for chronic hepatitis C nonresponder patients are correlated with the inhibition of IFN-␥ secretion (3,18,34). Our results revealed that HCV NS5A affects Gata-3 and Tbx21 expression and impairs IFN-␥ production (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…This is the first time in which all of the HCV proteins are expressed in the same context by a single virus vector. Usually, the HCV vaccine candidates target the structural proteins (Core, E1, and E2) (42)(43)(44)(45), a combination of structural and nonstructural proteins (Core, NS3, and NS4) (46)(47)(48), or the nonstructural proteins (generally NS3, NS4, and NS5) (20,25). Undoubtedly, the most frequently used HCV antigen is NS3 since the majority of the viral epitopes recognized by cytotoxic T lymphocytes and CD4 ϩ T cells in patients with HCV infection are located in this protein (9,49).…”
Section: Discussionmentioning
confidence: 99%
“…However, HCV envelope proteins demonstrate the highest sequence variability, with regard to HCV genetic variants, among all viral proteins (Sobolev et al, 2000). Though the immunization with the full-size HCV envelope proteins can elicit virus-neutralizing antibodies, these antibodies are specific to certain HCV genetic variants, relative to the one, from which the envelope proteins used for immunization, are taken (Elmowalid et al, 2007;Alvarez-Lajonchere et al, 2009). Several highly conserved sites were determined in HCV envelope proteins E1 and E2 (Sobolev et al, 2000); however, most these sites did not elicit specific antibodies because of insufficient Tlymphocyte help resulting from the absence of T-helper epitopes in the vicinity.…”
Section: Peptide Immunogens For Anti-hcv Vaccines Under Developmentmentioning
confidence: 99%